2013
DOI: 10.1371/journal.pone.0065698
|View full text |Cite
|
Sign up to set email alerts
|

Leprdb/db Mice with Senescence Marker Protein-30 Knockout (Leprdb/dbSmp30Y/−) Exhibit Increases in Small Dense-LDL and Severe Fatty Liver Despite Being Fed a Standard Diet

Abstract: Background/AimsThe senescence marker protein-30 (SMP30) is a 34 kDa protein originally identified in rat liver that shows decreased levels with age. Several functional studies using SMP30 knockout (Smp30Y/−) mice established that SMP30 functions as an antioxidant and protects against apoptosis. To address the potential role of SMP30 in nonalcoholic fatty liver disease (NAFLD) pathogenesis, we established Smp30Y/− mice on a Leprdb/db background (Leprdb/dbSmp30Y/− mice).Research Design/Principal FindingsMale Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Eight‐week‐old Lepr db/db Smp30 Y/− male mice were given vitamin C‐supplemented water and a standard diet (340 kcal/100 g, fat 5.6%) for 16 weeks. We found, first, that hepatic SMP30 mRNA and protein levels in Lepr db/db Smp30 Y+ were significantly lower than in Lepr db/+ Smp30 Y/+ mice, suggesting that the SMP30 level is affected by overeating‐induced obesity and obesity‐related diseases . We also reported that hepatic SMP30 mRNA levels were significantly lower in C57BL/6CrSlc female mice fed a diet of highly saturated fatty acids (60% fat) for 8 weeks compared with recipients of a normal diet (4.5% fat) .…”
Section: Smp30 Knockout Leprdb/db Mice As a Novel Model Of Nashmentioning
confidence: 73%
See 2 more Smart Citations
“…Eight‐week‐old Lepr db/db Smp30 Y/− male mice were given vitamin C‐supplemented water and a standard diet (340 kcal/100 g, fat 5.6%) for 16 weeks. We found, first, that hepatic SMP30 mRNA and protein levels in Lepr db/db Smp30 Y+ were significantly lower than in Lepr db/+ Smp30 Y/+ mice, suggesting that the SMP30 level is affected by overeating‐induced obesity and obesity‐related diseases . We also reported that hepatic SMP30 mRNA levels were significantly lower in C57BL/6CrSlc female mice fed a diet of highly saturated fatty acids (60% fat) for 8 weeks compared with recipients of a normal diet (4.5% fat) .…”
Section: Smp30 Knockout Leprdb/db Mice As a Novel Model Of Nashmentioning
confidence: 73%
“…Lepr db/db Smp30 Y/− mice showed increases of small, dense LDL‐cholesterol content, but a decrease of high‐density lipoprotein cholesterol levels compared with Lepr db/db Smp30 Y/+ mice, although plasma levels of total cholesterol were similar in both strains (Fig. ) . The quantitative reverse transcription polymerase chain reaction analysis showed that amounts of hepatic LDL and VLDL receptor mRNA were significantly lower in Lepr db/db Smp30 Y/− mice than those of Lepr db/db Smp30 Y/+ mice .…”
Section: Smp30 Knockout Leprdb/db Mice As a Novel Model Of Nashmentioning
confidence: 90%
See 1 more Smart Citation
“…Both SMP‐30‐knockout mice on a Lepr db/db background as well as SMP30/superoxide dismutase‐1 double‐knockout mice developed hepatic steatosis and presented higher levels of hepatic oxidative stress and superoxide anion radicals compared with WT mice. These findings were attributed to decreased levels of hepatic apolipoprotein B and transcription factors involved in lipid metabolism . Similarly, NASH induction by methionine and choline‐deficient diet into p53‐deficient male mice resulted in slower disease progression accompanied by lower ROS accumulation and lipid peroxidation as well as fewer apoptotic cells compared with the WT mice .…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 96%
“…The functional activities of SMP30 include its involvement in intracellular calcium pumping [5], cell-to-cell junction formation [6], organophosphatase activity [7], and lactonase activity in relation to vitamin C biosynthesis in rodents [8]. Interestingly, it has been reported that SMP30-deficient mice are more susceptible to UV-or cigarette-smoke-induced stress and that they are vulnerable to lung diseases, such as emphysema [9,10], hepatic hyperlipidemic diseases [11,12], cataract formation [13], and pancreatic insulin-release problems [14]. In addition, the finding of the upregulation of oxidative stressrelated protein carbonyls in the lung of the SMP30 knockout mouse further expanded physiological roles for SMP30 [10].…”
Section: Introductionmentioning
confidence: 99%